Acute presentation of intestinal malrotation in adults: a report of two cases - Hanna, Thomas (Ann R Coll Surg Engl, 2010)
INTRODUCTION: Intestinal malrotation is a rare developmental abnormality occurring as a result of incomplete rotation during fetal life. It usually presents in the first few weeks of life, but may persist unrecognised into adult life. We report two interesting cases in elderly patients both characterised by a significant diagnostic challenge due to atypical clinical and radiological signs and in one case an unusual complication following laparotomy. CASE REPORTS: The first case was a 64-year-old man initially treated for diverticulitis but at laparotomy was found to have malrotation of the midgut and a perforated left-sided appendicitis. The second case was a 76-year-old woman admitted with multiple fractures and increasing abdominal distension following a fall. Ten days after admission, she underwent right hemicolectomy to treat faecal peritonitis due to multiple caecal perforations complicating volvulus in the presence of midgut malrotation. CONCLUSIONS: These cases illustrate challenges associated with managing patients with undiagnosed intestinal malrotation. Delayed diagnosis is a common feature in several case reports describing atypical presentation of appendicitis in patients with malrotation. While abdominal CT scan can remove much of the diagnostic uncertainty, the diagnosis of malrotation can be missed unless there is a high index of suspicion.